Video Pembelajaran Berbasis Wondershare Filmmora pada Materi Bagian Tubuh Tumbuhan Muatan Pembelajaran IPA Kelas IV - Rapitasari, Ni Putu Ratih Novi; Ganing, Ni Nyoman (Journal for Lesson and Learning Studies, 2022)
The lack of application of Wondershare Filmmora-based learning video media reduces students' understanding of learning concepts in science learning content. This study aimed to develop a learning media in the form of a learning video based on Wondershare Filmmora on the subject matter of plant body parts for class IV SD science learning content. This type of development research uses the ADDIE development model. Data collection methods used are observation, interviews, questionnaires, and tests. The subjects in this study consisted of 1 design expert, 1 content expert, 1 instructional design expert, 1 instructional media expert, 3 individual test subjects, and 9 small group test subjects. The data analysis technique used is a quantitative descriptive technique. The results of learning video media development based on Wondershare Filmmora on science learning content in class IV SD are declared valid. The results of the assessment of engineering experts are very well qualified (90.00%). The content expert's assessment results are very well-equipped (96.00%). The results of the assessment of instructional design experts are well qualified (89.33%). The results of the evaluation of learning media experts are well qualified (89.33%). The results of the individual test assessment are very well qualified (97.33%), and the small group is very well qualified (96.15%). The implications of this research are empirically proven by using Wondershare Filmmora-based instructional video media to increase students' conceptual understanding of the material on plant body parts.